Draft Annual Plan 1986-87 Vol. III (In 4 Volumes) Haryana State - Planning Commission (Planning Commission, 1985)
An outlay of Rs.40828 lakhs was approved in the draft VII Five Year Plan for Major Medium and Multipurpose River valley Projects. Out of this Rs. 40840 lakhs is for Major Medium Irrigation Schemes, and Rs. (-) 12 lakhs for Multipurpose River valley projects viz. Unit I & II of the Beas Project. The work on the Beas Project Unit I & II has been practically completed, as such a nominal provision of Rs. (-)12 lakhs was made to account for Haryana's share receipts from this project under Irrigation Component.
Planning Department, Government of Haryana